Cytogenetics of two species of Paratelmatobius (Anura: Leptodactylidae), with phylogenetic comments - Lourenço, Luciana B.; Garcia, Paulo C. A. [UNESP]; Recco-Pimentel, Shirlei M. (Springer Nature, 2000)
In this paper we provide a cytogenetic analysis of Paratelmatobius cardosoi and Paratelmatobius poecilogaster. The karyotypes of both species showed a diploid number of 24 chromosomes and shared some similarity in the morphology of some pairs. On the other hand, pairs 4 and 6 widely differed between these complements. These karyotypes also differed in their NOR number and location. Size heteromorphism was seen in all NOR-bearing chromosomes of the two karyotypes. In addition, both karyotypes showed small centromeric C-bands and a conspicuous heterochromatic band in the short arm of chromosome 1, although with a different size in each species. The P. cardosoi complement also showed other strongly stained non-centromeric C-bands, with no counterparts in the P. cardosoi karyotype. Chromosome staining with fluorochromes revealed heterogeneity in the base composition of two of the non-centromeric C-bands of P. cardosoi. Comparison of the chromosomal morphology of these Paratelmatobius karyotypes with that of P. lutzii showed that the P. poecilogaster karyotype is more similar to that of P. lutzii than P. cardosoi. These cytogenetic results agree with the proposed species arrangements in the P. cardosoi and P. lutzii groups based on morphological and ecological data.
Keywords: animal cell; cell heterogeneity; centromere; chromosome 1; chromosome C band; chromosome number; cytogenetics; diploidy; ecology; female; frog; gene location; genetic polymorphism; karyotype; male; morphology; nonhuman; phylogeny; Animals; Bufonidae; Chromosome Banding; Chromosomes; Cytogenetics; DNA, Ribosomal; Female; In Situ Hybridization, Fluorescence; Karyotyping; Male; Nucleolus Organizer Region; Phylogeny; Ploidies; Sex Factors; Amphibia; Animalia; Anura; Leptodactylidae; Paratelmatobius; Paratelmatobius cardosoi; Paratelmatobius lutzii; Paratelmatobius poecilogaster; Reptilia